Human-based nanocomposite cryogels for hemostatic and wound healing applications - Mendes, Bárbara B. (2019)
In trauma surgery, a fast and effective hemostatic agent is crucial to prevent death. The current used hemostatic sponges are highly effective in stopping the hemorrhages, however they have a limited stability, shape memory, and biological functionality to induce an efficient regenerative healing after injury. Blood derivatives have attracted great attention as an inexpensive milieu of bioactive molecules (e.g., growth factors, cytokines), self-assembling scaffolding proteins (e.g., fibrinogen, fibronectin, vitronectin), and antimicrobial peptides (e.g., platelet factor-4) that have the ability to enhance angiogenesis, stem cell recruitment, and tissue regeneration. Among those, platelet lysate (PL) has attracted great attention as a milieu of supra-physiological doses of biomolecules that can be easily standardized. However, the current PL scaffolds showed limited stability and weak mechanical strength, which severely limits its performance as a bioinstructive and hemostatic biomaterial. Herein, we propose the use of aldehyde-functionalized CNC (a-CNC) that will be crosslinked through reversible Schiff base bonds established with the amine groups of PL proteins to produce a stable hemostatic cryogel for wound healing applications.